2011
DOI: 10.1111/j.1440-1843.2011.01960.x
|View full text |Cite
|
Sign up to set email alerts
|

EMMPRIN (CD147) regulation of MMP‐9 in bronchial epithelial cells in COPD

Abstract: The increased EMMPRIN expression in COPD is reflected by an increased release from bronchial EC, which are one of the main source of EMMPRIN. EMMPRIN regulates MMP-9 expression in COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…Our results provide the first evidence of an overexpression of EMMPRIN in endothelial cells and inflammatory cells following TBI. Previous reports have shown that EMMPRIN induces the expression of several MMPs in an autocrine and paracrine manner to degrade the basement membrane of the original vessel and remodel the extracellular matrix (ECM) around neovasculature sites (Huet et al, 2008;Koga et al, 2011) and that the functional importance of EMMPRIN was mainly related to its ability to induce MMPs (Jouneau et al, 2011). In the present study, we found increased MMP-9 expression in the injured cortex.…”
Section: Discussionmentioning
confidence: 51%
“…Our results provide the first evidence of an overexpression of EMMPRIN in endothelial cells and inflammatory cells following TBI. Previous reports have shown that EMMPRIN induces the expression of several MMPs in an autocrine and paracrine manner to degrade the basement membrane of the original vessel and remodel the extracellular matrix (ECM) around neovasculature sites (Huet et al, 2008;Koga et al, 2011) and that the functional importance of EMMPRIN was mainly related to its ability to induce MMPs (Jouneau et al, 2011). In the present study, we found increased MMP-9 expression in the injured cortex.…”
Section: Discussionmentioning
confidence: 51%
“…The main sources of MMP-9 are usually neutrophils, alveolar macrophages [36] and lung epithelial cells [37]. A possible reason for increased serum MMP-9 levels could be that the absence of the CD200 results in enhanced susceptibility of lung epithelial cells to the action of elastase and LPS.…”
Section: Discussionmentioning
confidence: 99%
“…In the adult, Ig-CAMs regulate the recruitment and subsequent activation of circulating lymphocytes, studies show they are also expressed in the epithelium and vasculature of the bronchial mucosa and levels of two Ig-CAMs, ICAM-1 and CD44 (hyaluronic acid receptor), are increased in the epithelium of asthmatics [130,131]. Recent data also suggests a third Ig-CAM, CD147 (EMMPRIN -Extracellular matrix Metalloprotease Inducer) is increased in the epithelium of patients with chronic obstructive pulmonary disease (COPD) [132]. CD147 is over-expressed by metastatic cells of the skin, bladder, breast, and lung [92].…”
Section: Igcams In Asthma Repair and The Effects Of Il-13mentioning
confidence: 93%
“…Airway epithelial CD147 expression is increased in murine models of lung injury [136] and in several inflammatory airway diseases including pulmonary fibrosis [137] and interstitial pneumonias, where increased CD147 is associated with MMP-2, -7 (matrilysin) and -9 levels in the lungs of patients [138]. Recent studies have demonstrated CD147 is increased in the airway epithelium and BAL of patients with COPD, and signaling via CD147 regulates MMP-9 expression in cultured bronchial epithelial cells [132]. CD147 is potentially important in asthma; in a mouse model of allergic asthma, inhalation of a CD147-neutralizing monoclonal antibody reduced ovalbumin (OVA)-induced airway mucin production and airway hyperreactivity, whilst partially inhibiting the recruitment of eosinophils and effector CD4 + T cells into lung tissue [139].…”
Section: Igcams In Asthma Repair and The Effects Of Il-13mentioning
confidence: 99%
See 1 more Smart Citation